Pengaruh Penerapan Akuntansi Berbasis Akrual dan Kompetensi Sumber Daya Manusia terhadap Kualitas Laporan Keuangan Pemerintah Daerah: Studi Empiris pada Satuan Kerja Perangkat Daerah (SKPD) Kabupaten Solok Selatan - Fibriani, Rani; Deviani, Deviani (Universitas Negeri Padang, 2025)
This study aims to determine the effect of the application of accrual-based accounting and human resource competencies on the quality of the financial statements of the regional government of South Solok Regency (South Solok Regency Regional Work Unit). The type of data in this study is primary data obtained from questionnaires distributed to employees or financial staff in the Regional Work Unit (SKPD) of South Solok Regency. Data analysis was done using quantitative analysis with the IBM SPSS Statistics 27 program. The sample in this study was 82 respondents with a purposive sampling technique. The results showed that the application of accrual-based accounting had a significant effect on the quality of South Solok Regency local government financial reports. Human resource competence also has a significant effect on the quality of the financial statements of the local government of South Solok Regency. For further researchers, it can add other variables that are relevant and predicted to affect the quality of local government financial reports.